2008
DOI: 10.1103/physrevb.78.054440
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectroscopic investigation on the coupling of electronic and magnetic structure in multiferroic hexagonalRMnO3(R=Gd, Tb, Dy, and Ho) t

Abstract: We investigated the effects of temperature and magnetic field on the electronic structure of hexagonal RMnO 3 (R = Gd, Tb, Dy, and Ho) thin films using optical spectroscopy. As the magnetic ordering of the system was disturbed, a systematic change in the electronic structure was commonly identified in this series. The optical absorption peak near 1.7 eV showed an unexpectedly large shift of more than 150 meV from 300 K to 15 K, accompanied by an anomaly of the shift at the Néel temperature. The magnetic field … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 32 publications
5
17
0
Order By: Relevance
“…The spin flip is accompanied with resonant electronic excitation of d-d transition, i.e., the electronic excited d state with m s = −2 can be much more easily achieved. This is consistent with the temperature dependent study of on-site d-d transition, which showed that the transition has a blueshift of~0.1 eV with cooling in the antiferromagnetic state [106,107]. This blueshift is attributed to the differences in exchange interaction in the excited and ground states of a given Mn 3+ ion [106].…”
Section: Broad Linewidthsupporting
confidence: 90%
“…The spin flip is accompanied with resonant electronic excitation of d-d transition, i.e., the electronic excited d state with m s = −2 can be much more easily achieved. This is consistent with the temperature dependent study of on-site d-d transition, which showed that the transition has a blueshift of~0.1 eV with cooling in the antiferromagnetic state [106,107]. This blueshift is attributed to the differences in exchange interaction in the excited and ground states of a given Mn 3+ ion [106].…”
Section: Broad Linewidthsupporting
confidence: 90%
“…In Figure 2b, the absorption peak shows an abrupt change around the Néel temperature. Such anomalies of absorption peak shifts were observed in hexagonal RMnO 3 thin films with R = Gd, Tb, Dy, Ho and Lu [12]. These anomalies are attributed to that the electronic state is modulated by the antiferromagnetic ordering.…”
Section: Optical Transition Propertymentioning
confidence: 66%
“…Accordingly, the optical transitions occur from the e 1g and e 2g states to a 1g state [39]. It is widely considered that the absorption peak at~1.7 (2.3) eV is originated from the optical transition from the e 2g to a 1g (e 1g to a 1g ) states [12,37,39]. The absorption band shows a lower energy shift with an increase in temperature.…”
Section: Optical Transition Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…study including the origins of ferroelectric ordering and antiferromagnetic (AFM) ordering, the microscopic mechanisms of the anomalous dielectric constant, blueshift of the Mn d to d transition energy (E dd ), and the magnetoelectric (ME) effect near the Néel temperature (T N ) [1][2][3][4]. In particular, through temperature-dependent high-resolution neutron scattering experiments, the ME coupling in this family of multiferroics was further identified to involve a significant magneto-elastic effect [4].…”
mentioning
confidence: 99%